2022
DOI: 10.1186/s12959-022-00402-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of venous thromboembolism and evaluation of a modified caprini risk assessment model: a single-centre, prospective cohort study involving patients undergoing lung resections for bronchiectasis

Abstract: Background Venous thromboembolism (VTE) is a common postoperative complication in general thoracic surgery, but the incidence of patients undergoing surgery for bronchiectasis was not known. The purpose of our study was to investigate the incidence of VTE in bronchiectasis patients undergoing lung resection and to evaluate the risk stratification effect of the modified caprini risk assessment model (RAM). Methods We prospectively enrolled patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Zhou et al 20 revealed that the Caprini score identifies 84.3% of VTE cases, whereas the Padua Prediction score only identifies 49.1% of VTE cases, besides, the Caprini risk level is associated with in-hospital and 6-month mortality. Chen et al 21 observed VTE in 10 of 117 patients who underwent pneumonectomy, and Caprini score is proportional to the VTE ratio, indicating the superior performance of Caprini score in predicting VTE. Thence, serial assessment of perioperative Caprini scores is effective in reducing the incidence of thrombosis and mortality of critically ill patients, improving patient prognosis and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al 20 revealed that the Caprini score identifies 84.3% of VTE cases, whereas the Padua Prediction score only identifies 49.1% of VTE cases, besides, the Caprini risk level is associated with in-hospital and 6-month mortality. Chen et al 21 observed VTE in 10 of 117 patients who underwent pneumonectomy, and Caprini score is proportional to the VTE ratio, indicating the superior performance of Caprini score in predicting VTE. Thence, serial assessment of perioperative Caprini scores is effective in reducing the incidence of thrombosis and mortality of critically ill patients, improving patient prognosis and quality of life.…”
Section: Discussionmentioning
confidence: 99%